(untitled) (Progressive Agriculture, 2013)
Studies were conducted to identify Aeromonas sp. isolates collected from disease affected carp fishes (Cyprinus carpio and Labeo rohita), their antibiotic sensitivity pattern and sensitivity to 121 herb extracts. A total of 19 Aeromonas sp. isolates were identified from a total of 84 different isolates through a series of physiological, morphological and biochemical tests. Seven antibiotics viz., streptomycin, chloramphenicol, erythromycin, sulphamethoxazole, cephradine, oxytetracycline and gentamycin were tested by disc diffusion method where all of the Aeromonas sp. isolates were found sensitive to streptomycin, erythromycin and gentamycin. But, 78.95% of the isolates were found resistant to oxytetracycline. In addition, 5%, 11%, and 16% isolates exhibited resistance to chloramphenicol, cephradine and sulphamethoxazole, respectively. Twenty one percent of the isolates showed multiple resistance to the antibiotics. A total of 121 herb extracts were evaluated for their sensitivity to the fish pathogenic Aeromonas sp. isolates. Among these, 23 herbs were found to possess antimicrobial activity. Leaf extracts of Eugenia caryophyllus, Spondias pinnata and Terminalia chebula were found to inhibit the growth of all the Aeromonas sp. isolates. In this study, multiple antibiotic resistant isolates were also found to be sensitive to several herb extracts. Thus, herbal treatment would promise a greater viable solution for effective treatment of fish disease. DOI:http://dx.doi.org/10.3329/pa.v21i1-2.16758 Progress. Agric. 21(1 & 2): 117 - 129, 2010